The Agogô in the Technological Age: Ethical and Cultural Transformations Among the Ika Society - IKECHUKWU MONDAY OSEBOR & DORA IFEANYI OKUNBOR (Journal of Dharma, 2025)
The Agogô is a traditional musical instrument of the Ika people of Delta State, Nigeria, performed during festivals, ceremonies, dances and storytelling. It sustains rhythm while deepening the spiritual and cultural texture of community events. In the technological age, however, the creativity and expression surrounding the Agogô are being reshaped in ways that raise ethical and religious concerns. This article examines how technological interventions affect the artistic life of the Agogô. Using philosophical analysis, the authors argue that technology has aided documentation, dissemination and preservation of the instrument, while simultaneously contributing to cultural dilution and commodification. Safeguarding the Agogô, therefore, requires frameworks that hold innovation accountable to cultural heritage and promote inclusive, culturally grounded development of digital tools and artistic practices for the common good. The article concludes that a native-centric ethical approach, rooted in community values and cultural respect, is essential for addressing technological impacts and protecting the integrity of this heritage.